Dynamic Standing Exercise using the Innowalk Device in Patients with Genetic and Acquired Motor Impairments - Ana Pekanovic; Walter Strobl; Ulrich Hafkemeyer; Jens Kleine; Peter Bernius; Rolf Burghardt; Caroline Schmidt-Lucke (Medical Journals Sweden, 2022)
Objective: For individuals with motor impairments, dynamic standing has been proposed as an opportunity for regular daily physical activity. The aim of this study was to analyse patient characteristics, indications, intensity of usage, desired objectives and outcomes of dynamic standing in daily clinical practice in order to form the basis for research regarding this treatment option. Setting: Data were analysed from standardized questionnaires completed prospectively before supply of a home-based medical device for dynamic standing (Innowalk; Made for Movement GmbH, Langenhagen, Germany) and at the time of individual adaptations. Participants: In a retrospective chart analysis, records of 46 patients (50% cerebral palsy; 50% diverse syndromes) were evaluated. Intervention: The Innowalk had been prescribed for either home-based use (n = 31), in therapeutic institutions (n = 8), or other settings (n = 7). Dynamic standing was performed for 10-30 min as a single session (n = 8) or for 20-60 min 11 [4-21] weeks in 36 patients. Results: Improvements were found for: passive assisted motion (79%), stimulation of intestinal functions (71%), body stability (64%), joint mobility (56%), secure means of allowing supine position (52%), and revision of abnormal motion patterns (48%). Conclusion: Thus, this systematic approach shows usage patterns, indications, desired goals and clinical outcome of dynamic standing in daily clinical practice and forms the basis for the design of a prospective, randomized controlled trial. LAY ABSTRACT This study analysed usage patterns, safety, desired goals and the effects of the Innowalk, a medical device that enables a patient to stand in a weight-bearing position while stimulating active use of upper thigh and torso muscles in order to maintain patient's balance. In addition, the characteristics of patients who used this device were summarized and described. Half of the included patients employed the Innowalk due to cerebral palsy. The positive effects after usage of the Innowalk were noticed to occur in passive assisted motion, stimulation of digestive function, body stability, joint mobility, secure means of allowing horizontal body position, and correction of abnormal motion patterns. No negative effects were noticed. Use of the Innowalk was safe. Further research is needed to verify the effectiveness of the usage of the medical device.